GrNFS: A granular neuro-fuzzy system for regression in large volume data - Simiński, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Neuro-fuzzy systems have proved their ability to elaborate intelligible nonlinear models for presented data. However, their bottleneck is the volume of data. They have to read all data in order to produce a model. We apply the granular approach and propose a granular neuro-fuzzy system for large volume data. In our method the data are read by parts and granulated. In the next stage the fuzzy model is produced not on data but on granules.
Keywords: granular computing; neuro-fuzzy systems; large volume data; machine learning